Intellectual Friendship in Architectural Design Education - Hurol, Yonca (University of Illinois Press, 2004)
The objective of this paper is to discuss the effects of authoritarian and friendly attitudes of teachers on the design creativity of students in architectural education. The paper contains literary and comparative research on the relation between the authoritarian role of the teacher and the design psychology of the student which affects creativity. A theoretical base is formed for the category of ‘intellectual-friendship’ which already exists in architectural education. Is it possible to refuse ‘authoritarian limits’ in order to provide a better medium for ‘creativity’?
The claim of this article is that supporting the individuality and the intellectuality of the student increases the creativity during architectural design education.
Keywords: architectural education, design education, individual, intellectuality